2018
DOI: 10.1177/0300060518814999
|View full text |Cite
|
Sign up to set email alerts
|

Does vibration benefit delayed-onset muscle soreness?: a meta-analysis and systematic review

Abstract: Objective Delayed-onset muscle soreness (DOMS) is a symptom of exercise-induced muscle injury that is commonly encountered in athletes and fitness enthusiasts. Vibration is being increasingly used to prevent or treat DOMS. We therefore carried out a meta-analysis to evaluate the effectiveness of vibration in patients with DOMS. Method We searched nine databases for randomized controlled trials of vibration in DOMS, from the earliest date available to 30 May 2018. Visual analogue scale (VAS) and creatine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…Different techniques have shown certain positive effects in the recovery process, with proven effects such as reduction of delayed onset muscle soreness (DOMS), maintenance of sports performance, reduction of pain and many others [ 2 ]. These include manual therapy (MT) [ 3 ], mechanical vibration (MV) [ 4 ] or the foam roller (FR) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques have shown certain positive effects in the recovery process, with proven effects such as reduction of delayed onset muscle soreness (DOMS), maintenance of sports performance, reduction of pain and many others [ 2 ]. These include manual therapy (MT) [ 3 ], mechanical vibration (MV) [ 4 ] or the foam roller (FR) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, massage has been shown to prevent and decrease muscle pain [ 7 ]. While MT is the most traditional technique, other treatments such as MV have recently shown positive effects on muscle recovery, particularly in reducing DOMS [ 8 ] and reducing serum creatine kinase concentrations [ 4 ]. Thus, MV is now considered a therapeutic intervention technique for muscle recovery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that vibration may optimise muscle performance by synchronising motor unit activity and increasing blood flow and that this may prevent mechanical sarcoma disruption and in turn reduce DOMS [ 26 – 28 ]. The overall picture is encouraging, with meta-analysis finding vibration effective for prevention or treatment of DOMS [ 29 , 30 ]. Therapies studied include those provided before [ 31 – 36 ] and after [ 9 , 20 , 35 , 37 – 49 ] exercise; in athletes [ 36 , 49 ], untrained [ 9 , 31 35 , 37 , 38 , 40 , 42 , 45 , 47 , 48 ] and recreationally active [ 20 , 39 , 41 , 43 , 44 , 46 ] participants; and using local vibration [ 20 , 31 , 32 , 34 , 35 , 37 , 38 , 40 , 45 , 48 , 49 ] and WBV [ 9 , 33 , 36 , 39 , 41 44 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on vibration stimulation can be characterized as whole-body vibration and local vibration, the former is more commonly used than the latter, and together they provide multifrequency and multiamplitude vibration modes. 4,5 Further, a study showed that whole body vibration is positively associated with delayed onset of muscle soreness and decreased athletic performance ability, 6 as well as increased muscle strength and muscle fatigue relaxation both during and after excises or training. 7,8 However, strong evidence for these reported outcomes remains limited by insufficient sample size and study designs.…”
Section: Introductionmentioning
confidence: 99%